Evaluasi Strategi Bersaing Travel Haji dan Umrah PT. Amanah Travel Indonesia untuk Meningkatkan Jumlah Jemaah - Fiola Arista Widya; Septria Susanti (Lembaga Yasin AlSys, 2026)
The increasingly intense competition in the Hajj and Umrah travel industry in Bukittinggi City has affected fluctuations in the number of pilgrims, particularly at PT Amanah Travel Indonesia, thus requiring an evaluation of the competitive strategies implemented by the company. This study aims to evaluate the competitive strategies used and to identify the most effective strategy for improving the company’s competitiveness and the number of pilgrims. This study employed a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation with informants consisting of leaders, employees, and pilgrims, and were then analyzed through data reduction, data display, and conclusion drawing. The results showed that PT Amanah Travel Indonesia implemented several competitive strategies, namely cost leadership, differentiation, focus, and a hybrid strategy. The cost leadership strategy was implemented through operational efficiency and the setting of affordable package prices. The differentiation strategy was realized through intensive worship services and the use of experienced mutawif. The focus strategy was directed at the segment of first-time and elderly pilgrims. Meanwhile, the hybrid strategy became the most dominant strategy because it was able to combine affordable prices with good service quality. This study concludes that the hybrid strategy is the most effective strategy for increasing the number of pilgrims. The implications of this study underscore the importance of improving service consistency, innovating digital promotion, and strengthening service quality to increase pilgrims’ trust and loyalty.